2016
DOI: 10.1002/2015jb012741
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic friction in sheared fault gouge: Implications of acoustic vibration on triggering and slow slip

Abstract: Friction and deformation in granular fault gouge are among various dynamic interactions associated with seismic phenomena that have important implications for slip mechanisms on earthquake faults. To this end, we propose a mechanistic model of granular fault gouge subject to acoustic vibrations and shear deformation. The grain‐scale dynamics is described by the Shear‐Transformation‐Zone theory of granular flow, which accounts for irreversible plastic deformation in terms of flow defects whose density is govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 53 publications
2
18
1
Order By: Relevance
“…This is consistent with the findings of Lieou et al [17,25]. However, due to the strain localization in our simulations the stick-slip is only confined to the banded domain.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This is consistent with the findings of Lieou et al [17,25]. However, due to the strain localization in our simulations the stick-slip is only confined to the banded domain.…”
Section: Discussionsupporting
confidence: 83%
“…While shear induced dilation has been coined as rate strengthening, the non-montonic volume response in the presence of vibration points to possible transition into rate weakening and accordingly loss of sliding stability. This has been successfully demonstrated by Lieou et al [17,25] who explored stick-slip dynamics under a wide range of strain rates and confining pressures and discovered a transition from fast stick-slip to slow stick-slip and ultimately stable sliding as a function of increasing vibration intensity. However, in these previous studies it was observed that the stability properties before the application of external vibrations are recovered upon cessation of vibration and apparently no lasting rheological changes occurred.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…(If the granular layer is subjected to external vibration, there is an extra term corresponding to the rate at which vibration pumps energy into the system. This term can be neglected if we restrict our analysis to an unvibrated granular layer [ Lieou et al , ]). The latter is encapsulated in the transport coefficient scriptK(χ), which must be nonnegative because of the second law of thermodynamics; it includes dissipation due to inelastic collisions and friction between grains.…”
Section: Theoretical Model Of Shear Transformation Zonesmentioning
confidence: 99%